Prevalence of low birth weight and maternal risk factors at a tertiary care hospital: A cross-sectional study - Sharma, Arvind; Patel , Sunita; Aprajita; Lodhi , Prince (Asian Journal of Medical Sciences, 2025)
Background: Birth weight is a key public health indicator reflecting infant survival, maternal health, and healthcare quality. Low birth weight (LBW) is associated with significant risks, including cognitive and motor delays, neurodevelopmental disorders, congenital anomalies, sepsis, respiratory distress, insulin resistance, dyslipidemia, and hypertension. Aims and Objectives: This study aims to assess the prevalence of LBW and identify factors contributing to LBW. Materials and Methods: This hospital-based cross-sectional study was conducted at a tertiary care hospital in Jabalpur, Madhya Pradesh, over 6 months. Data were collected postnatally from mothers of live newborns using a pre-tested questionnaire covering demographics, antenatal care (ANC), obstetric history, and neonatal characteristics. Result: A total of 5133 newborns were included in the study and prevalence of LBW at 41.3% was reported. Prevalence of LBW was significantly higher among mothers under 24 years (43.4%), with lower education (44.7%), underweight (50.4%), tobacco use (54.3%), alcohol use (64.4%), <4 ANC (46.0%), anemia (48.3%), shorter birth intervals (50.7%), and preterm births (51.0%). Conclusion: Despite various maternal and neonatal health programs, LBW remains a significant public health challenge, influenced by multiple maternal factors such as young age, low educational attainment, poor nutritional status, inadequate ANC, tobacco and alcohol use, anemia, and preterm delivery.